2019
DOI: 10.1029/2018gl081359
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Wettability of Sandstones: Addressing Conflicting Capillary Behaviors

Abstract: Understanding the capillary and wetting behavior of supercritical CO2 (scCO2) and brine in reservoir rocks is crucial for reliable predictions of geologic carbon storage, as it strongly impacts CO2 migration and residual trapping in the reservoir. The wetting state of such systems can be assessed through laboratory measurements of the capillary pressure characteristic curve. However, while some studies reported consistent scaling with strongly water wet systems, some others observed deviations from hydrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The core flooding setup is similar to the one used in previous experiments (Krevor et al, ; Ni et al, ; Perrin & Benson, ) and details can be found in the supporting information (Text S1, Figure S1). The core was not fired before the experiment, due to the low clay content (Shipton et al, ) and because previous studies have shown that firing in CO 2 /water/sandstone (with low clay content) system does not change experimental results and wetting properties (Garing & Benson, ). The core was first dried in the oven for several days and then wrapped using the same layering protocol as for the single phase experiment (section ).…”
Section: Methodsmentioning
confidence: 99%
“…The core flooding setup is similar to the one used in previous experiments (Krevor et al, ; Ni et al, ; Perrin & Benson, ) and details can be found in the supporting information (Text S1, Figure S1). The core was not fired before the experiment, due to the low clay content (Shipton et al, ) and because previous studies have shown that firing in CO 2 /water/sandstone (with low clay content) system does not change experimental results and wetting properties (Garing & Benson, ). The core was first dried in the oven for several days and then wrapped using the same layering protocol as for the single phase experiment (section ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, time‐dependent changes in brine wettability after extended exposure (periods of months) to CO 2 have been observed for limestone sands, and along with increasing in CO 2 pressure, correlated to increased volumes of capillary trapped CO 2 (Wang & Tokunaga, ). However, this phenomenon remains poorly understood, and other authors have found results for similar systems to the contrary (Garing & Benson, ). Time‐dependent wetting alteration may well be an important factor when attempting to translate core‐scale results to the reservoir.…”
Section: Resultsmentioning
confidence: 91%
“…Advancements in X‐ray imaging and microtomographic techniques have enabled in situ contact angle measurements thus providing direct insight into wetting behavior (e.g., Wildenschild & Sheppard, ); however, these are limited in their volume of investigation (typically mm 3 ). At the larger core scale (several centimeters), inferences regarding wettability are largely taken from capillary pressure curves (e.g., Garing & Benson, ) or relative permeability behavior (e.g., Al‐Menhali et al, ) with saturation measured by X‐ray or volumetric methods (Saeedi et al, ). One alternative approach for studying fluid wettability in rock cores is via nuclear magnetic resonance (NMR) relaxometry measurements which are inherently sensitive to brine‐surface interactions (e.g., wetting) and can also provide quantitative saturation information.…”
Section: Introductionmentioning
confidence: 99%
“…Past experimental studies have shown that N 2 is an excellent analogue for CO 2 . Although contact angle and surface tension values are different in N 2 /water and CO 2 /water systems, it has been shown that in both conditions the rocks are strongly water-wet and the difference in wetting states can be corrected for, in multiphase flow analysis (Al-Menhali et al, 2015;Garing and Benson, 2019;Niu et al, 2015;Pini and Benson, 2013;Plug and Bruining, 2007).…”
Section: Multiphase Core Flooding Experiments With Medical Ct Scannermentioning
confidence: 99%